Effect of Moringa oleifera L. Leaf Extract on GPx-3 Gene Expression in the Brain of Induced Ethylene Glycol on Rats (Rattus norvegicus) - Nasution, Niska Maulida; Idami, Zahratul; Widiarti, Leni; Ningrum, Nurlian Augustin (Universitas Pattimura, 2026)
Ethylene glycol is one of the toxic substances commonly used as solvents and is known to induce oxidative stress in neural tissue. GPX-3 is an antioxidant enzyme that works to reduce ROS, maintain redox balance, and protect cells from damage caused by free radicals produced during oxidative stress processes. This study aims to evaluate the effect of administering Moringa oleifera L. leaf extract after ethylene glycol induction on the intensity of GPx-3 gene expression in the brain of white rats (Rattus norvegicus). This research employed a completely randomized design (RAL) using 20 rats divided into five groups: a normal control group, a 0.75% ethylene glycol group, a 150 mg/kgBW Mo group, a 300 mg/kgBW Mo group, and a 450 mg/kgBW Mo group. The research stages included brain RNA extraction, cDNA synthesis, PCR amplification, agarose gel electrophoresis, and band intensity analysis using ImageJ. The results showed that GPx-3 gene expression in rat brain tissue appeared at 300 bp. Administration of Moringa oleifera L. leaf extract increased GPx-3 gene expression intensity in ethylene glycol induced rats, with the most prominent increase observed in treatment 2 (300 mg/kgBW). The increase or decrease in measured expression after normalization to GAPDH indicates that the observed changes reflect a biological response to treatment rather than technical error. This study presents a novelty finding by demonstrating, for the first time, the dose-dependent modulation of GPx-3 gene expression in brain tissue following ethylene glycol induced oxidative stress and identifying 300 mg/kgBW as the most effective dose, thereby revealing a potential molecular mechanism underlying the neuroprotective effect of Moringa oleifera L. leaf extract.